Identitas Budaya Bugis Dalam Kumpulan Cerpen Sala Dewi Karya Emil Amir Serta Pemanfaatannya Sebagai Alternatif Pembelajaran Sastra Di Sma - Hamidah, Nur Sufi; Sukatman, Sukatman; Murti, Fitri Nura (Lingua Skolastika, 2024)
This study aims to describe and explain the Bugis culture which exists in the collection of Sala Dewi's short stories by Emil Amir. It was chosen because it has contain values of viscous local culture, character building that can be used as a role model for students, and each short story has good reputation, so this collection can be told has good credibility. This study is uses a descriptive qualitative method with an ethnographic research design that uses the Spradley data analysis method. Words, phrases, sentences, or paragraphs are the source of the data which represent physical culture, social system, cultural system, and cultural values of Bugis culture. This research adapted from Koentjaraningrat's theory. The data were collected by documentation and interview, and analyzed by using the Spradley analysis method, including domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The results of this study shows that the four forms of Bugis culture in the collection of Sala Dewi's short stories are mutually sustainable, spread over four short stories, and expressed through inter-character dialogue, character monologues, or character narratives. Hereinafter, the results of this study were used as teaching materials in the XI grade of senior high school students in Indonesian as a part of Language and Literature materials.